Nostalgia in the Global City: Recuperating the Battler in the Sydney Production of Cloudstreet (Journal of the Association for the Study of Australian Literature, 2013)
The article speculates towards reading the total 'event' of the theatrical version of Cloudstreet, including the adaptation of the novel and the critical and popular reception of the play--as a symptomatic Australian cultural text.